Continuous regulation of wind energy power system permitting protection of the system components against wind over-speed. Issue 5 (October 2022) - Tounsi, Souhir
In this paper is presented a methodology of design and control of an electromagnet braking system dedicated to the protection of the wind energy production systems against the strong rise of the current in the power chain attached to the strong elevation of the wind speed. This methodology focuses on the dimensioning of the electromagnet acting as a mechanical brake and its integration into the wind energy generation system. The electromagnet is designed jointly by the analytical method offering the advantages of compatibility with large-scale optimization approaches and the finite element method for verifying and increasing the accuracy of the analytical model. This study essentially involves the design and modeling phase of the electromagnet dissociated from the wind turbine and then by the phase of its integration with the wind turbine. The global model associating the electromagnet and the wind turbine controlled with a view to ensuring a continuous recharging of energy accumulator at a constant current equal to the nominal current of which the wind turbine is sized, is implanted under the Matlab-Simulink simulation environment. The results of simulations are encouraging and open the research trail to optimization work of the entire chain.